2005
DOI: 10.1016/j.immuni.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways and Genes that Inhibit Pathogen-Induced Macrophage Apoptosis— CREB and NF-κB as Key Regulators

Abstract: Certain microbes evade host innate immunity by killing activated macrophages with the help of virulence factors that target prosurvival pathways. For instance, infection of macrophages with the TLR4-activating bacterium Bacillus anthracis triggers an apoptotic response due to inhibition of p38 MAP kinase activation by the bacterial-produced lethal toxin. Other pathogens induce macrophage apoptosis by preventing activation of NF-kappaB, which depends on IkappaB kinase beta (IKKbeta). To better understand how p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
259
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(277 citation statements)
references
References 57 publications
13
259
2
3
Order By: Relevance
“…PAI-2 expression in monocytes and macrophages is up-regulated rapidly, mainly through IKK/NF-κB activation, after stimulation with inflammatory mediators and pathogens (13). PAI-2 suppresses apoptosis and IL-1β-driven inflammation, although the underlying mechanisms are poorly understood (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-2 expression in monocytes and macrophages is up-regulated rapidly, mainly through IKK/NF-κB activation, after stimulation with inflammatory mediators and pathogens (13). PAI-2 suppresses apoptosis and IL-1β-driven inflammation, although the underlying mechanisms are poorly understood (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PAI-2 has been associated with newly identified uPA-independent biological functions, probably through targeting an as yet uncharacterized intracellular molecule (11). In addition, PAI-2 is one of the major molecules up-regulated in macrophages in response to TLR4 activators or inflammatory mediators, suggesting its function in the regulation of innate immunity (12,13).…”
mentioning
confidence: 99%
“…However, CREB has recently been found to be phosphorylated downstream of p38 [65], and CREB can also be phosphorylated downstream of ERK1/2. In both cases, CREB is not phosphorylated directly by MAPK, but by MSK1/2, kinases activated by either the ERK1/2 or p38 MAPK [25,26,66]. It is worth noting that for some stimuli, including LPS, the inhibition of ERK1/2 and also p38 is required to block MSK activation and CREB phosphorylation [25].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that transcription of the serpin plasminogen activator inhibitor 2 (PAI-2) is induced by the cooperation of both CREB and NF-kB. 7 A new function of IKK1 has been identified in macrophages. Two different groups showed that whereas IKK2 is involved in NF-kB activation in macrophages, IKK1 actually inhibits NFkB activation in these cells.…”
Section: Nf-jb and Macrophage Activitymentioning
confidence: 99%